Contribution to the knowledge of Cybocephalid beetles Biology and ethology of Cybocephalus freyi Endrody-Younga (Bollettino di zoologia agraria e bachicoltura, 2024)
Cybocephalid beetles are predators of armored scale in sects. Up to the present they have been poorly studied in ltaly. In this p aper we give notes on the biology and the Iife cycle of Cybocephalus freyi Endrody-Younga, a species common in Sardinia and Liguria.